2016
DOI: 10.1186/s12913-016-1505-4
|View full text |Cite
|
Sign up to set email alerts
|

Influences on uptake of cancer screening in mental health service users: a qualitative study

Abstract: BackgroundCancers are a leading cause of death worldwide. People with mental illness are 30 % more likely to die from cancer than the general population. One reason for this may be low uptake of nationally offered cancer screening tests by people with mental illness. We aimed to identify barriers and facilitators for breast, cervical and bowel cancer screening uptake by people with mental illness in order to inform interventions to promote equal access.MethodsThe interview study was conducted in both urban and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(97 citation statements)
references
References 37 publications
(44 reference statements)
3
93
1
Order By: Relevance
“…The findings are in accordance with those of previous smaller sample studies and in studies from other care settings. [63][64][65][66][67][68] The effect size for the distance variables in this study was small overall (close to 1) compared with those reported in the other studies, probably because we adjusted for more potentially confounding variables and the interference of the other important service variables.…”
Section: Main Findingscontrasting
confidence: 70%
“…The findings are in accordance with those of previous smaller sample studies and in studies from other care settings. [63][64][65][66][67][68] The effect size for the distance variables in this study was small overall (close to 1) compared with those reported in the other studies, probably because we adjusted for more potentially confounding variables and the interference of the other important service variables.…”
Section: Main Findingscontrasting
confidence: 70%
“…Together with our theoretical arguments, this evidence suggests that reduced executive functioning will challenge sick people in relation to interacting with the state, which may be one explanation for empirical findings of reduced take‐up of public services and benefits among sick people. For instance, some estimates suggest that those with mental health problems are 30 percent more likely than the general public to die from cancer (Clifton et al ); lower take‐up of public screening programs is one explanation for this gap (Aggarwal, Pandurangi, and Smith ; Clifton et al ). Furthermore, studies of the Supplemental Security Income program have shown that many disabled people fail to access the program (Benitez‐Silva, Buchinsky, and Rust ), partly because the neediest eligible citizens struggle with the program's lengthy and complicated application process (Currie ), and those with severe disabilities are most affected when compliance costs increase (Deshpande and Li ).…”
Section: The Human Capital Catch‐22: Life Factors That Create Need Fomentioning
confidence: 99%
“…In relation to cancer screening, a Cochrane review 17 found that no intervention to promote uptake has been tested in people with SMI. This is important since qualitative work 18 indicates there are specific barriers to cancer screening uptake in people with SMI and that interventions effective in the general population may not be effective in the SMI population. Furthermore, barriers to screening uptake or access may vary for different types of screening, at different stages of the screening process and between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, barriers to screening uptake or access may vary for different types of screening, at different stages of the screening process and between individuals. 18 …”
Section: Introductionmentioning
confidence: 99%